Pemodelan Farmakofor, Skrining Virtual dan Docking Kandidat Inhibitor Baru Protein Tirosin Kinase VEGFR2 - Saudale, Fredy Z (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2020)
VEGFR2 (Vascular Endothelial Growth Factor Receptor 2) plays a key role on tumor angiogenesis. Inhibition of VEGFR2 mediated-biological signaling pathways by chemical compounds has been considered as an effective therapeutic option for cancer treatment. This study aims to identify new candidates of VEGFR2 inhibitor compounds using the method of computational molecular modeling (in silico) namely pharmacophore analysis, virtual screening and docking. From the results it is identified that N-(1-chloro-9,10-dioxoanthracen-2-yl)-2,6-difluorobenzamide shows a higher affinity (-9.8 kcal/mol) to the VEGFR2 receptor protein compared to urea derivative inhibitor used as positive control (-9.0 kcal/mol). Interactions between N-(1-chloro-9,10-dioxoanthracen-2-yl)-2,6-difluorobenzamide with VEGFR2 are stabilized through a hydrogen bond with Cys917 at a distance of 2 Å, hydrophobic interactions with Glu883, Glu915, and π-sigma interactions with Val914 and Leu838. Toxicity prediction by the Ames method shows that N-(1-chloro-9,10-dioxoanthracen-2-yl)-2,6-difluorobenzamide is not mutagenic but may induce damages to the liver. Further validation and optimization of structure and activity of N-(1-chloro-9,10-dioxoanthracen-2-yl)-2,6-difluorobenzamide are needed not only to verify its inhibiting potential and but also to optimize its safety and selectivity for cancer drug development.